PENDEKATAN FOLLOW THE MONEY DALAM PENELUSURAN TINDAK PIDANA PENCUCIAN UANG SERTA TINDAK PIDANA LAIN - Sutrisni, Ni Komang; Sukranatha, Anak Agung Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 02, Februari 2013, 2013)
Follow the money system in the money laundering and other crimes investigation is a new step that is applied in the context of the law enforcement process. Purpose of this paper is to find out what it means to follow the money approach in tracking crime, as well as to know how to approach prospects follow the money in search of money laundering and other offenses. In this study, using normative legal research and case approach. Follow the money approach to prioritize follow the money making money or assets compared with the proceeds of crime seeking criminals. After the results obtained, and then sought the culprit and criminal offenses commited. In search of proceeds of crime, financial analysis approach used. Thus, an effective way to combat crime is effective cooperation between the law enforcement agencies that had seemed rather disjointed. For that, we need a shared understanding and cooperation in the use of new approaches follow the money as a complement to conventional approaches follow the suspect, one of which is to conduct joint training among law enforcement.
Keywords: System, Follow the Money, Search, criminal